ANALYSIS OF SOCIAL CONFLICTS IN FOSTER THE PEOPLE’S SONG PUMPED UP KICKS - Mikail, Izzaditya Dharmaputra; Saputra, Hadi; Kusuma, Albert Wijaya; Pasopati, Rommel Utungga; Hariyono, Hariyono (Universitas Negeri Surabaya, 2025)
The song of Pumped Up Kicks, released by Foster the People in 2010 draws public attention, both because of its melody and dark lyrical theme. This song creates discussions about social isolation, mental health, and violence among teenagers. This paper aims to analyze the song through the qualitative approach and the perspective of social conflicts. By interpreting the lyrics and their deeper implications, this research explores the effects of neglect, bullying, depression, economic disparity, and mental health issues in this song. It highlights how the widening gap between the rich and the poor, along with broken relationships between parents and children, can push youth toward destructive behavior. In conclusion, this analysis suggests that Pumped Up Kicks serves as a powerful social commentary and reminder of the pressing societal issues people face today, emphasizing the urgent need for awareness and intervention.